A new antipatharian-associated species of the genus Cuapetes Clark, 1919 (Crustacea: Decapoda: Palaemonidae) and a new record of C. nilandensis (Borradaile, 1915) from Japan - Okuno, Junji; Chan, Tin-Yam (Zootaxa, 2012)
Two antipatharian-associated species of the pontoniine shrimp genus Cuapetes Clark, C. lanceolatus sp. nov. and C.nilandensis (Borradaile), are reported from the Ryukyu Islands, Japan. The new species appears closest to C. akiensis(Kubo) and C. calmani (Tattersall), but differs considerably from the latter two species in the shape of the rostrum and thelength of upper antennular flagellum. Cuapetes nilandensis, the type species of the genus, is recorded from Japanese waters for the first time.